High CD163 Expression on Classical Monocytes Is Associated with Immune Control of HBV Infection in Noncirrhotic Patients - Anna Parfieniuk-Kowerda; Kamil Grubczak; Andrzej Eljaszewicz; Magdalena Świderska; Magdalena Maciaszek; Anatol Panasiuk; Jerzy Jaroszewicz; Robert Flisiak; Marcin Moniuszko (Hindawi Limited, 2020)
Background and Aims. The functional impairment of monocytes may contribute to the persistence of HBV infection. This study aims to assess monocyte subpopulations, monocyte expression of CD163, plasma sCD163, and sTWEAK in patients with chronic HBeAg-negative HBV infection at different phases of disease. Methods. Fifty-nine patients with CHB, 9 with a history of HBsAg/anti-HBs seroconversion, were enrolled. The control group consisted of 15 healthy volunteers. Subpopulations of peripheral blood monocytes were distinguished by CD14 and CD16. Membrane expression of CD163 was assessed by flow cytometry, plasma sCD163 concentration by ELISA, and sTWEAK by bead-based multiplexed immunoassay system. Results. CD163 expression was increased in classical and intermediate monocytes in CHB patients and those with HBsAg/anti-HBs seroconversion. CD163 expression on classical monocytes was associated with status of immune control and thus significant in HBV infection as compared to active hepatitis. Plasma sCD163 concentration was increased in CHB patients and those with HBsAg/anti-HBs seroconversion vs. the control group. Positive correlations between plasma sCD163 and ALT, as well as APRI, were observed. Plasma sTWEAK concentration was lower in CHB patients in comparison to patients with HBsAg/anti-HBs seroconversion. Conclusions. Exposure to HBV antigens alters monocyte subsets' frequencies and activation. The expression of CD163 on classical monocytes increased in parallel with improved immune control of the HBV infection. Patients who seroconverted HBsAg had the highest expression of CD163 on monocytes, which suggests involvement of monocytes in immune control of HBV infection. Persistent inflammation is accompanied by higher CD163 expression and sCD163 level and lower sTWEAK level.